Chiral Recognition and Separation by Chirality‐Enriched Metal–Organic Frameworks. (12th June 2018) - Das, Saikat; Xu, Shixian; Ben, Teng; Qiu, Shilun
Abstract: Endowed with chiral channels and pores, chiral metal–organic frameworks (MOFs) are highly useful; however, their synthesis remains a challenge given that most chiral building blocks are expensive. Although MOFs with induced chirality have been reported to avoid this shortcoming, no study providing evidence for the ee  value of such MOFs has yet been reported. We herein describe the first study on the efficiency of chiral induction in MOFs using inexpensive achiral building blocks and fully recoverable chiral dopants to control the handedness of racemic MOFs. This method yielded chirality‐enriched MOFs with accessible pores. The ability of the materials to form host–guest complexes was probed with enantiomers of varying size and coordination and in solvents with varying polarity. Furthermore, mixed‐matrix membranes (MMMs) composed of chirality‐enriched MOF particles dispersed in a polymer matrix demonstrated a new route for chiral separation. Abstract : Preiswerte achirale Bausteine und rückgewinnbare chirale Dotanden wurden zur Synthese von chiralitätsangereicherten MOFs (CE‐MOFs) genutzt. Die Bildung von Wirt‐Gast‐Komplexen zwischen den CE‐MOFs und Alkoholenantiomeren ist abhängig von der Größe, Koordinationsweise und Lösungsmittelpolarität. Mixed‐Matrix‐Membranen aus in einer Polymermatrix dispergierten CE‐MOF‐Partikeln sind außerdem für die Enatiomerentrennung geeignet.